2022-RA-637-ESGO Five-year universal tumor screening of BRCA1/2 in epithelial ovarian carcinoma;is histotype-directed hr-deficiency testing justified?. (20th October 2022) - Kramer, Claire JH; Lanjouw, Lieke; Elst, Arja ter; Solleveld-Westerink, Nienke; Hazelbag, Hans M; Kagie, Marjolein J; Ahsmann, Els JM; van der Hout, Annemieke H; van der Stoep, Nienke; de Kroon, Cor D; Gaarenstroom, Katja N; van Wezel, Tom; et al.
Abstract : Introduction/Background: A popular dogma is that in epithelial ovarian carcinomas (EOCs) mutations in BRCA1/2 and other homologous recombination (HR)-genes are exclusive to high-grade serous ovarian carcinomas (HGSOC). Nevertheless, the European guidelines recommend germline or tumor screening, regardless of histotype. Here, we report on the results of five-year prospective, universal 'tumor-first' screening of BRCA1/2 and HR-genes in EOC and assess the relationship between identified mutations and histotypes. Methodology: EOCs were prospectively sequenced between September 2017 and December 2021 in two university medical centers in The Netherlands. The gene-panel included BRCA1/2 and for a large subset of cases the panel was expanded with EOC-susceptibility HR-genes BRIP1, PALB2, RAD51C and RAD51D. All mutations (class 4 and 5 variants) were reported. Prior to sequencing, all EOC underwent a central pathology review by expert gynecopathologists. Results: The universal 'tumor-first' screening strategy was executed in the two centers on a total of 831 EOCs ( table 1 ). In total, 73% were HGSOCs and 27% were EOC-cases of other histologies. The overall yield for BRCA1/2 mutations in EOC was 13%, and the vast majority of mutations (94.5%) were identified in HGSOCs (yield of 17%; table 1 ). Intriguingly, 6/221 (2.7%) non-HGSOCs, i.e., n=3 high-grade endometroid, n=1 low-grade endometrioid and n=2 low-grade serous OC, harboured a BRCA2 mutation. No BRCA1/2 or HR-gene mutations were identified in clear cell and mucinous carcinomas. The results of extensive HRD testing of these six outliers will be presented at the meeting, including loss of heterozygosity, functional RAD51 assay and copy-number signatures. Conclusion: This large 'real-world' cohort of centrally revised and prospectively sequenced EOCs confirmed that BRCA1/2 mutations are almost exclusively identified in HGSOC. Extensive HRD testing will inform us about the clinical relevance of the identified BRCA1/2 and HR-gene mutations beyond HGSOCs and whether histotype-directed HRD-screening, after central pathology revision, may be justified.